Species composition of small mammals at the Ayer Hitam Forest Reserve, Puchong, Selangor - Hussin, Mohamed Zakaria; Sundai, Silang; Mudin, Rahim (Universiti Putra Malaysia Press, 2001)
A study on the species composition and abundance of small mammals was carried out in Ayer Hitam Forest Reserve (AHFR), Puchong, Selangor. A total oj 1120 trapping-hours recorded 14 species of small mammals which belonged to 11 genera From five families and three orders. The taxa comprised of six murids, Jour sciurids, three insectivores and one primate. A total of 32 indiciduals of smalls mammals were captured. From this, 17 individuals or 53% were rats, 9 individuals (28 %) were squirrels, 4 individuals tree shrews (13 %) and 1 individual each (3 %) Jor both primate and gymnures. The order Rodentia (rats and squirrels) was the main group of small mammals in the area, with a total capture of 82% or 26 individuals.